The Style of the Quran Between Sentence Syntax and Text Syntax - Bin Tahir, Mohamed Mohamed ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2014)
This study explores the field of applied linguistics by examining its scientific foundations and interdisciplinary nature, highlighting its presence in the Arab intellectual heritage through the example of Ibn Al-Ajdabi. The research emphasizes that applied linguistics goes beyond language acquisition and teaching, intersecting with various disciplines such as psychology, sociology, education, geography, and language policy. It addresses the development of linguistic teaching materials, the resolution of language learning challenges, and translation studies. The study asserts that applied linguistics functions as a bridge between numerous fields related to language, demonstrating that the Arab heritage offers valuable contributions and insights for applied linguistic analysis.